IP multimedia services analysis of mobile IP and SIP interactions in 3G networks. - Faccin, S.M (IEEE Communications magazine)
Third-generation cellular networks have been designed to provide a variety of IP data services. Both IPv4 and IPv6 are supported in order to provide future-proof solutions. Mobility is supported through both cellular-specific and IP mechanisms. Mobile IP is becoming a key technology for managing mobility wireless networks. At the same time, the session initiation protocol is the key to realizing and provisioning services in IP-based cellular networks. The need for mobility of future real-time service independent of terminal mobility requires SIP to seamlessly interwork with mobile IP operations. In this article, we investigate the issues related to interworking between SIP and mobile IP, with a focus on IPv6 and the applicability to 3G networks being standardized in 3GPP and 3GPP2.